Mutation, clonal fitness and field change in epithelial carcinogenesis. Issue 3 (November 2014) - Frede, Julia; Adams, David J; Jones, Philip H
Abstract Developments in lineage tracing in mouse models have revealed how stem cells maintain normal squamous and glandular epithelia. Here we review recent quantitative studies tracing the fate of individual mutant stem cells which have uncovered how common oncogenic mutations alter cell behaviour, creating clones with a growth advantage that may persist long term. In the intestine this occurs by a mutant clone colonizing an entire crypt, whilst in the squamous oesophagus blocking differentiation creates clones that expand to colonize large areas of epithelium, a phenomenon known as field change. We consider the implications of these findings for early cancer evolution and the cancer stem cell hypothesis, and the prospects of targeted cancer prevention by purging mutant clones from normal‐appearing epithelia. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.